2004
DOI: 10.1177/1069072703257753
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Work Setting Congruence on Well-Being

Abstract: This study investigates the influence of two aspects of person-environment congruence on well-being: occupational congruence (OC), the subject of numerous studies, and an entirely new concept, congruence with the physical conditions of the workplace (work setting congruence) (WSC). Using a sample of 164 men and women employed in seven of Roe's eight occupational fields, significant correlations, all in the expected direction, were found between WSC and well-being measures (i.e., satisfaction, burnout, and anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Studies on direct relationship between person -work environment fit and employees' health are sparse, but bring interesting results. Misfit between an employee and his/her work environment results in elevated job stress [8,9], depression [10], anxiety [10,11], burnout [11] or decreased ability to take up physical and mental effort at work [12]. In this paper, the authors examine a relationship between one of the aspects of person-work environment fit which is called Person-Organization fit (P-O fit) and health P-O fit is defined by Kristof [13] as "the compatibility between people and organizations that occurs when: (a) at least one entity provides what the other needs, or (b) they share similar fundamental characteristics, or (c) both" (p. [4][5].…”
Section: Objectivementioning
confidence: 99%
“…Studies on direct relationship between person -work environment fit and employees' health are sparse, but bring interesting results. Misfit between an employee and his/her work environment results in elevated job stress [8,9], depression [10], anxiety [10,11], burnout [11] or decreased ability to take up physical and mental effort at work [12]. In this paper, the authors examine a relationship between one of the aspects of person-work environment fit which is called Person-Organization fit (P-O fit) and health P-O fit is defined by Kristof [13] as "the compatibility between people and organizations that occurs when: (a) at least one entity provides what the other needs, or (b) they share similar fundamental characteristics, or (c) both" (p. [4][5].…”
Section: Objectivementioning
confidence: 99%
“…These points have been evidenced in a variety of occupational categories. As an example, Lachterman and Meir (2004) found that work-setting congruence significantly contributed to worker well-being across a range of occupational groups. In a study addressing newly employed nurses, Laschinger and Grau (2012) found that multiple dimensions of workplace congruence had a significant impact on physical and mental health outcomes, along with symptoms related to burnout.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, since person-environment fit has been mostly studied in the workplace, not many studies have mentioned the relationship of fit with variables other than job attitudes or organizational outcomes even though life satisfaction is an important measure of subjective well-being, and happiness introduces positive outcomes (Lachterman & Meir, 2004). In this study, high person-environment fit was expected to have positive influence on life satisfaction.…”
Section: Life Satisfactionmentioning
confidence: 86%
“…For most people, work is an important part of life (Rain, Lane, & Steiner, 1991) and it is expected to play a critical role in the assessment of life quality. Holland's (1985) congruence theory has been tested by several researchers who have highlighted the significant relation between congruence and well-being measures (Lachterman & Meir, 2004). For example, when an employee's preferences have been met by the work environment, positive outcomes such as job, occupation, and work setting satisfaction are expected (Lachterman & Meir, 2004).…”
Section: Life Satisfactionmentioning
confidence: 99%